2018
DOI: 10.24270/uuom.2018.27.4
|View full text |Cite
|
Sign up to set email alerts
|

Upprifjunaráfangar framhaldsskóla í stærðfræði: Skapandi og krefjandi vinna eða stagl?

Abstract: Í greininni eru könnuð viðhorf framhaldsskólakennara til viðfangsefna er lúta að gagnrýninni og skapandi hugsun í upprifjunaráföngum í stærðfræði. Byggt er á viðtalsrannsókn þar sem fimm kennarar úr þremur framhaldsskólum tóku þátt. Tekin voru viðtöl bæði áður en og eftir að kennararnir lögðu verkefni fyrir nemendur í upprifjunaráföngum, þar sem beita þurfti gagnrýninni og skapandi hugsun við lausnaleit. Kennsluáætlanir áfanga voru einnig greindar. Niðurstöðurnar benda til þess að viðhorf kennaranna til slíkra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…These results contrasted with teacher concerns about older students' struggles to engage meaningfully in whole-class mathematical discussions (Leikin et al, 2006). However, more recent studies of teacher perceptions have shown less concern and generally a more positive attitude to posing challenging tasks involving teacher-facilitated discussion (Russo & Hopkins, 2019;Sigurjónsson & Kristinsdóttir, 2018). Thus, mathematics teachers seem to increasingly agree that facilitating opportunities for meaningful engagement with mathematical concepts through cognitively activating instruction is both desirable and good practice.…”
Section: Cognitive Activationmentioning
confidence: 99%
“…These results contrasted with teacher concerns about older students' struggles to engage meaningfully in whole-class mathematical discussions (Leikin et al, 2006). However, more recent studies of teacher perceptions have shown less concern and generally a more positive attitude to posing challenging tasks involving teacher-facilitated discussion (Russo & Hopkins, 2019;Sigurjónsson & Kristinsdóttir, 2018). Thus, mathematics teachers seem to increasingly agree that facilitating opportunities for meaningful engagement with mathematical concepts through cognitively activating instruction is both desirable and good practice.…”
Section: Cognitive Activationmentioning
confidence: 99%